Validity of Meaningful Practical Activity Sheets for Basic Electronics Material on Voltage and Current Divider Circuits Based on Project Based Learning - Pertiwi, Novia Ayu Sekar; Husna, Asiyah Lu’lu'ul; Miruki, Siti Sukowati Wanafaktu (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
Every learning process, both theory and practice, needs to implement meaningful learning. This also applies to students. Ideally, students are expected to carry out meaningful practicums, namely carrying out practicums by understanding the theory underlying the practicum, each step taken in the practicum, and being able to connect the results of the practicum with real implementation in everyday life. The reality in the field, in the implementation of basic electronics practicums, students only carry out practicums mechanically according to the instructions without understanding the theoretical concepts underlying the steps and have not been able to link the results of the practicum with its implementation in the real world. Voltage divider and current divider circuits are basic electronics theories with familiar implementations in everyday life with various uses in electronic devices. Efforts to solve this problem are to carry out practicums by applying the PjBL model which is synergized with meaningful learning. The steps of the learning activities are outlined in the meaningful practicum activity sheet (meningfull practice) basic electronics based on project based learning on voltage and current divider circuits. Before the practicum activity sheet is used in learning, its validity needs to be tested so that the activity sheet used by students later is a valid activity sheet. This research is a Research and Development (R&D) research with the ADDIE development model which is implemented in three stages, namely Analysis, Design, Development. This research is intended for Physics Education students of KH University. A. Wahab Hasbullah who are or have taken basic electronics courses, both theory and practice. In general, the Meaningful Practical Activity Sheet (Meningfull Practice) Basic Electronics Material Voltage and Current Divider Circuits Based on Project Based Learning is declared valid and can be used after being revised according to the validator's input.